2014
DOI: 10.1016/j.forsciint.2013.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Facial approximation of ‘Angel’: Case specific methodological review

Abstract: A forensic facial approximation is typically undertaken to generate further leads to identity of the deceased, and over the past ten years there has been a considerable increase in the number of verified relationships concerning the skull and likely facial appearance. This paper describes the evidence and methods used to approximate the face and facial features of a young woman whose remains were found in the Belanglo State Forest (New South Wales, Australia) in August 2010. A review of methodologically analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
(111 reference statements)
0
11
0
1
Order By: Relevance
“…Both in the forensic report that accompanied the facial approximation and in the publication that describes the methods [1] facial indices were calculated from the results. These indicated that:…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both in the forensic report that accompanied the facial approximation and in the publication that describes the methods [1] facial indices were calculated from the results. These indicated that:…”
Section: Discussionmentioning
confidence: 99%
“…(e35) The geometric morphometric evaluation of the facial approximation, relative to the average of the 64 database images (Table 3, However, not all of the methods that were applied in 2011 were verified methods. As discussed in the paper that describes the facial approximation [1], some were untested recommendations that have since been proven invalid, and not all aspects of the face have a verified method to apply. Furthermore, the geometric morphometric analyses also show that an assumption that there needed to be inter-feature agreement between the different methods is a false assumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations